Research on seismic exploration techniques and methods in urban environment of loess plateau. Issue 1 (February 2021) - Tian, A-Wei; Li, Zhong-Sheng; Liu, Si-Tong; Wang, Zhong-Sheng; Zheng, Ge-Hui; Yuan, Zi-Heng; Huang, Hua
Abstract: Seismic wave energy being absorbed strongly in thick loose loess stratum is a major problem that seismic exploration has to face. In the urban environment, this problem is particularly prominent due to the inability to use explosives, borehole explosion, and large-scale 3D observation methods to increase fold number. To solve this difficult problem, a series of seismic exploration effect tests were carried out in Shaoling Plateau, a southern suburb of Xi'an City. A large-tonnage vibroseis, 28-ton vibrator vehicle, was selected as seismic source. By comparing and analyzing the effects of various vibrating parameter of vibrator vehicle, cooperating with different model geophones acquisition, and using appropriate observation system, we had figured out the feasible parameters for the source excitation and data acquisition in the field working area. Based on the results of above test, a nearly 7 km long seismic survey line was completed with pretty good data acquisition, and the expected exploration aims were well achieved.